Flexible Titanium Nailing Versus Casting of Closed Unstable Tibial Shaft Fracture in Children and Adolescent (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Casting is the standard method of treatment for pediatric diaphyseal fracture of tibia. It has some limitations in treating an unstable fracture. Various options are available but still debate on optimal treatment strategy in 8-15 years age group. To compare the complications and Radiological Union of cast immobilization versus intramedullary nailing in the treatment of Children and adolescent with closed unstable tibial diaphyseal fractures.Materials and methods: This is a Quasi-Experimental study and patients aged between 8 to 15 years with unstable closed fracture of tibial shaft came to the Department of Orthopedic Surgery of CMCH were included. Eligible patients were allocated according to inclusion criteria selected for fracture management either by closed reduction and cast immobilization or by flexible intramedullary nailing. Patients were followed-up for at least six months after surgery and casting. Outcome measures were radiological union, complications and functional outcome were assessed by Flynn’s criteria at final follow-up. Data were collected with pretested structured case record form and analyzed by using SPSS26 with appropriate statistical methods. Results: Among58 patients, average mean ± SD age was 9.86 ± 1.91 (Range: 8-14) years. Most of the children (79.3%) were male in both groups. According to mode of injury, 72.4% was due to RTA. Associated fibular fracture was absent among 65.5% patients. According to types of fracture, short oblique was 58.6%, comminuted 17.2% and spiral 24.2%. There was no significant difference in complications among the two groups according to p value.  Mean ± SD union time in nailing group was 10.56 ± 1.21 and in casting group was 10.46 ± 1.41 weeks. After 6 months follow up, in nailing group, 21 (80.8%) patient’s functional outcome was excellent and 4 (15.4%) patient’s functional outcome was satisfactory and 1(3.8%) poor. In casting group, 17 (65.4%) patient’s functional outcome was excellent and 8 (30.8%) patient’s functional outcome was satisfactory and. 1(3.8%) poor. Functional outcome was better in nailing group, but statistically non-significant (p=0.416).  Conclusion: Despite the popularity of casting in the treatment of tibial shaft fracture in children and adolescent, present study shows flexible titanium nailing is safe and effective surgical approach of treatment for closed unstable tibial shaft fracture in children and adolescent age group. JCMCTA 2024 ; 35 (2) : 61-66